(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2023)
Introduction. The financial sector has traditionally been the most dynamic in terms of introducing new products, technologies, and innovations, including in the management sphere. One of the reasons for this is a lot of competition, and the intensification of globalization processes, which encourage financial institutions to be highly adaptable and efficient. In turn, they are determined by the quality of human capital, in particular, the level of its qualification and ability to develop, as well as the effective use of the potential of each employee. The purpose of the article. The purpose of the article is to theoretically summarize and update the competencies in demand of employees of financial institutions with a justification of methods for their assessment, taking into account the current requirements for staff skills in the current operating environment. Results. The article analyzes the most popular competencies of employees of financial institutions. The internal composition of professional, technical, digital, information, communication, creative, and adaptive employees competencies is detailed. The main stages of the process of evaluating the staff of financial institutions using a competency-based approach are described. The criteria for assessing the financial institutions’ staff within the key parameters (functional, behavioral, personal indicators, and characteristics) by which compliance with the position is assessed are determined. The main methods for evaluating the staff of financial institutions based on a competency-based approach are analyzed. The necessity of practical use of the above evaluation algorithms for the purpose of professional growth of both an individual employee and a financial institution as a whole is proved. Conclusiоns. The practical use of a competency-based approach to the assessment of financial institution personnel is an important stage in determining the professional level of an employee. The studied approach allows assessing the existing potential of employees with the aim of additional financial incentives for particularly valuable employees; formation of a personnel reserve; career advancement of talented employees; expansion of job responsibilities of individual employees; formation of an employee development program, and bringing their competencies in line with the modern requirements of a financial institution.